Principal's Leadership in Improving Teacher Professionalism and Graduate Quality - Slamet Pamuji; Isna Fatimatuz Zahroh; Siti Baro’ah; Arif Jalaludin (Universitas Nurul Jadid, 2025)
This study examines the role of the school principal as a manager in developing teacher professionalism and improving the quality of graduates at State Elementary School 2 Purwokerto Wetan. The research addresses the growing need for effective educational leadership in responding to the increasing demands of teacher competence and institutional quality. A qualitative case study approach was employed to explore leadership practices in a real educational setting. Data were collected through in-depth interviews, participatory field findings, and document analysis, and were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that the principal implements an integrated leadership strategy through training programs, learning supervision, specialized training, role modeling, and continuous professional development. These strategies contribute to improving teachers’ pedagogical competence, discipline, and professional commitment. The study also identifies several challenges, including limited resources, policy constraints, and varying levels of teacher motivation, which influence the effectiveness of professional development efforts. The findings highlight that teacher professionalism is most effectively developed through a continuous and systemic approach rather than isolated interventions. This study contributes to educational management by proposing an integrated model of principal leadership that emphasizes the combination of managerial practices and value internalization in fostering sustainable teacher professionalism and improving educational quality.